Persepsi Stakeholder Hasil Pengujian Sifat Biologi Tanah Produksi Biomassa untuk Pembangunan Pertanian Berkelanjutan di Kabupaten Probolinggo - Hendro Prasetyo; Zaenal Kusuma; Eny Dyah Yuniwati (Folium : Jurnal Ilmu Pertanian, 2023)
Soil damage by biomass production is a change in the basic properties of the soil in the area of biomass production caused by human actions. This study aims to analyze the damage to soil biomass production based on the biological characteristics of six sub-districts consisting of 12 villages in Probolinggo. The methods used are quantitative and qualitative methods, which include taking soil and plant samples, testing, surveis, interviews, and FGD (Focus Group Discussion). The results of the FGD data are used to determine stakeholder perceptions regarding information on soil properties. The results of the survei at the sampling location showed that the soil texture was moderate, the structure was hard, and the soil thickness was around 50-150 cm. Two villages had a low category bacterial population ranging from 5.5×105–7.3×105 cfu/gram and 5 villages had a very low category bacterial population ranging from 9.55×104–2.45×106 cfu/ grams. Mushroom populations from 7 villages have a very low category of 6.15×104–2.75×105 cfu/gram and 5 villages have a low category. Bacterial and fungal populations in 12 villages showed that soil damage had not occurred, indicating that the abundance of bacteria and fungi was above the critical threshold (<102 cfu/gram). The results of stakeholder perceptions show ignorance that soil biological properties are an indicator of soil damage and ignorance that the continuous use of chemical fertilizers can kill bacteria and fungi.